2010
DOI: 10.1038/aja.2009.87
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation of prostate cancer cell line, PC-3, in vitro and in vivo using (−)-gossypol

Abstract: We investigated the antiproliferative activity of (-)-gossypol on the human prostate cancer cell line PC3 in vitro and in vivo to elucidate its potential molecular mechanisms. Cell growth and viability were evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and cell apoptosis was detected by flow cytometry, terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) and electron microscopy. Expression of proliferating cell nuclear antigen (PCNA), Bcl-2, CD31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…In a recent study describing the inhibition of PC3 cells in vitro and in vivo, Zhang et al [48], used 2.5-10 lg/ml which corresponds to 9.6-38.6 lM of GP in vitro, whereas in their in vivo experiments they used 2.5-10 mg/kg corresponding to 2.5-10 ppm on a part per million basis (ppm). Because human GP consumption is limited by the FDA to 450 ppm [31] and GP is safe up to 70 mg/day (1 ppm for a 70 kg person) in human clinical trials [24], the concentration of GP used in our in vitro study (5-20 lM) is in the range of the therapeutic use of gossypol.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent study describing the inhibition of PC3 cells in vitro and in vivo, Zhang et al [48], used 2.5-10 lg/ml which corresponds to 9.6-38.6 lM of GP in vitro, whereas in their in vivo experiments they used 2.5-10 mg/kg corresponding to 2.5-10 ppm on a part per million basis (ppm). Because human GP consumption is limited by the FDA to 450 ppm [31] and GP is safe up to 70 mg/day (1 ppm for a 70 kg person) in human clinical trials [24], the concentration of GP used in our in vitro study (5-20 lM) is in the range of the therapeutic use of gossypol.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of angiogenesis by the combination of GP treatment and radiation markedly suppressed angiogenesis in PC3 xenografted cells in vivo [47]. Most importantly, recent study demonstrated that GP alone markedly decreased expression of angiogenic marker CD31, detecting the presence of capillary endothelial cells, in PC3 tumor xenografts [48]. Therefore, our study suggests that the inhibition of angiogenesis in vivo by GP is mediated by the suppression of VEGF secretion from PC3 cells, which results in the inhibition of capillary morphorgenesis of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used is the PC-3 (ATCC CLR-1435) cell line which is the cell line employed by us and reported on in the current paper. It is a human prostate cell line derived from metastatic prostate cancer in the bone [5,6]. It is characteristic of prostatic small cell carcinoma, the most common form of advanced prostate cancer [5,6].…”
mentioning
confidence: 99%
“…We previously found that ApoG2, a gossypol derivative, inhibits proliferation of prostate cancer cells both in vitro and in vivo and induces their apoptosis and autophagy (Zhang et al, 2010a;Zhang et al, 2010b). Although it is reported that the anti-tumor effect of ApoG2 in vivo is partially associated with the decrease of the microvessel density (Zhang et al, 2010a), the exact mechanism still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is related to angiogenesis and vascular invasion and thus inhibition of angiogenesis can be used as a method to treat prostate cancers (Weidner et al, 1993;Bagley et al, 2011;Gyftopoulos et al, 2011;Assadian et al, 2012;Lynch et al, 2012;Pande et al, 2012;Pinto et al, 2012). We previously found that ApoG2, a gossypol derivative, inhibits proliferation of prostate cancer cells both in vitro and in vivo and induces their apoptosis and autophagy (Zhang et al, 2010a;Zhang et al, 2010b). Although it is reported that the anti-tumor effect of ApoG2 in vivo is partially associated with the decrease of the microvessel density (Zhang et al, 2010a), the exact mechanism still remains unknown.…”
Section: Introductionmentioning
confidence: 99%